The politics of cultural appropriation in the contemporary USA - Menzel, Sarah (2018)
This thesis is an analysis of the underlying and overarching issues in the contemporary cultural appropriation debate focusing primarily on white appropriation of African American culture in the twenty-first century. It examines specific instances of appropriation and their consequences as well the significance of the broader sociocultural debate regarding appropriation. The implications of appropriating 'Black' hairstyles and of the case of Rachel Dolezal form the primary focal points for case study discussion. Other considerations are examined such as the historical trajectory of appropriation, varying forms of cultural exchange and possible explanations for why the appropriation debate has become particularly poignant in contemporary media and sociocultural discussions. The specifically racial nature of American history, ideas of otherness and the parallels between social and cultural politics are key discussion points which point to a larger narrative of racial essentialism and politicisation.